A COMPARISON OF GRAMMAR-TRANSLATION AND COMMUNICATIVE LANGUAGE TEACHING METHODS - Xujaqulova Aziza Uzbekistan State World Languages University The Second English Faculty 2nd-year student (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The field of language education has witnessed significant shifts in teaching methodologies over the past century, each reflecting evolving theories of language acquisition and changing educational priorities. Among the most influential and widely debated approaches are the Grammar-Translation Method (GTM) and Communicative Language Teaching (CLT). This article offers a comprehensive comparison of these two methods, examining their theoretical underpinnings, classroom implementations, the roles they assign to teachers and students, and their relative effectiveness in developing different aspects of language proficiency. The Grammar-Translation Method, rooted in classical education and structuralist theory, prioritises written language, translation, and grammatical accuracy. In contrast, Communicative Language Teaching, grounded in sociolinguistic and functional theories, emphasises interaction, fluency, and the practical use of language in authentic contexts. While GTM may foster strong reading and grammar skills, it often falls short in preparing learners for real-life communication. Conversely, CLT enhances communicative competence but may underemphasize grammatical precision if not carefully implemented. The article concludes that a hybrid approach that draws on the strengths of both methods may provide a more balanced and effective language learning experience, particularly in diverse EFL contexts.